Evaluating the efficacy of carbetocin versus oxytocin for preventing intraoperative blood loss, early postpartum hemorrhage, and maintaining a favorable hemodynamic profile in lower segment cesarean section: A prospective observational study - Bisma Fayaz; Raja Suhail Shounthoo; Ajaiz Rasool; Saima Wani; Showkat Ahmad Gurcoo (Asian Journal of Medical Sciences)
Background: Postpartum hemorrhage (PPH) remains a significant concern in obstetric practice, contributing substantially to maternal morbidity and mortality worldwide. Uterine atony, characterized by inadequate uterine muscle tone, constitutes approximately 70% of PPH cases. The initial step in medical management involves the use of uterotonic agents such as oxytocin, ergot alkaloids, and prostaglandins. However, their use is compounded by the accompanying side effects, hence the need for uterotonic agents with relatively better pharmacokinetic and pharmacodynamic profile continues. Carbetocin may require less additional uterotonic administration to manage blood loss compared to oxytocin alone. Carbetocin has a significantly longer half-life than oxytocin, potentially leading to more sustained uterine contractions and reduced blood loss.